Circadian clock—A promising scientific target in oral science - Feng, Guangxia; Zhao, Jiajia; Peng, Jinfeng; Luo, Beibei; Zhang, Jiaqi; Chen, Lili; Xu, Zhi (Frontiers in Physiology, 2022)
The oral and maxillofacial organs play vital roles in chewing, maintaining facial beauty, and speaking. Almost all physiological processes display circadian rhythms that are driven by the circadian clock, allowing organisms to adapt to the changing environment. In recent years, increasing evidence has shown that the circadian clock system participates in oral and maxillofacial physiological and pathological processes, such as jaw and tooth development, salivary gland function, craniofacial malformations, oral carcinoma and other diseases. However, the roles of the circadian clock in oral science have not yet been comprehensively reviewed. Therefore, This paper provides a systematic and integrated perspective on the function of the circadian clock in the fields of oral science, reviews recent advances in terms of the circadian clock in oral and maxillofacial development and disease, dialectically analyzes the importance of the circadian clock system and circadian rhythm to the activities of oral and maxillofacial tissues, and focuses on analyzing the mechanism of the circadian clock in the maintenance of oral health, affecting the common diseases of the oral and maxillofacial region and the process of oral-related systemic diseases, sums up the chronotherapy and preventive measures for oral-related diseases based on changes in tissue activity circadian rhythms, meanwhile, comes up with a new viewpoint to promote oral health and human health.